Combined Effects of UGT1A1 and SLCO1B1 Variants on Chinese Adult Mild Unconjugated Hyperbilirubinemia - Bai, Jie; Luo, Lei; Liu, Shuang; Liang, Chen; Bai, Li; Chen, Yu; Zheng, Sujun; Duan, Zhongping (Frontiers in Genetics, 2019)
The potential for genetic variation to cause adult unconjugated hyperbilirubinemia is increasingly being recognized. However, the cumulative effects of genetic variants have not been fully illuminated. The current study aimed to investigate the effects of Uridine diphospho-glucuronosyl transferase 1A1 (UGT1A1) and/or solute carrier organic anion transporter family member 1B (SLCO1B) polymorphic variants and their combined effects on mild unconjugated hyperbilirubinemia in Chinese adults. Fourteen genetic variants in the UGT1A1 or SLCO1B gene were genotyped through sequencing in 148 adults with unconjugated hyperbilirubinemia and 158 healthy controls. Variants c.-3275T>G, (TA)6>(TA)7, c.211G>A or c.1091C>T within the UGT1A1 gene as well as c.521T>C within the SLCO1B1 gene appear to be genetic risk factors for inherited unconjugated hyperbilirubinemia. After adjusting for covariates, the results of multivariate logistic regressions revealed that odds ratios (ORs) [(with 95% confidence interval (CI)] of these five variants were 2.35 (95% CI: 1.37-4.01, p=0.002), 2.38 (95% CI: 1.35-4.20, p=0.003), 2.99 (95% CI: 1.71-5.21, p<0.001), 7.60 (95% CI: 1.99-28.96, p=0.003), and 2.54 (95% CI: 1.27-5.11, p=0.009), respectively. The OR for unconjugated hyperbilirubinemia is positively correlated with the cumulative number of these five variants in adults. And the greater the number of genetic variations, the higher the total bilirubin level. Adults carrying diplotype 3/4 (homozygous c.-3275T>G and heterozygous (TA)6>(TA)7) had higher bilirubin levels than those with diplotypes 1/3 (heterozygous c.-3275T>G and (TA)6>(TA)7)) or 1/4 (heterozygous c.-3275T>G) (P<0.05). Similarly, bilirubin levels in individuals with diplotype 2/4 (heterozygous c.-3275T>G and c.211G>A) were higher than adults carrying diplotypes 1/2 (heterozygous c.211G>A) or 1/4 (P<0.001). For subjects with heterozygous or homozygous variant c.211G> A, as the number of c.521T>C alleles variation increased, the incidence of unconjugated hyperbilirubinemia increased, but it was not statistically significant. Our results indicate that variants of UGT1A1 and/or SLCO1B1 have combined effects on Chinese adult mild unconjugated hyperbilirubinemia.